The microbiology of arable soil surfaces - Jeffery, Simon (Cranfield University, 2007)
Whilst much is known about the physics and erosion of soil surfaces on a millimetre scale, little is known about the associated microbiology, particularly in temperate arable systems. The vast majority of research regarding microbial interactions at soil surfaces has concerned microbiotic crusts. However, such surface crusts take many years to form and then only in relatively undisturbed soil systems. Arable soil surfaces are subject to relatively extreme environmental conditions, potentially undergoing rapid changes in relation to temperature, water status and solar radiation compared to deeper soil zones. These extreme environmental parameters are likely to have a large impact on the biota found at the arable soil surface when compared to that which occurs in deeper soil zones. Phenotypic profiling using phospholipid fatty acid (PLFA) analysis, microbial biomass, and chlorophyll concentration were used to characterise soil microbial communities with the aim of quantifying differences within the surface layers of arable systems on a millimetre scale. This field work was supported with a series of microcosm-scale studies in which parameters such as length of time between disturbance events and the quality of light reaching the soil surface were controlled. Using microcosms subjected to simulated rainfall and imaged using X-ray computed tomography scanning, the effects of the soil surface microbiota on associated physical properties including structural integrity, porosity, erodibility and hydrological properties were investigated. This research showed that given sufficient time between disturbance events, environmental parameters such as temperature and wet:dry cycling were sufficient to drive the formation of a distinct soil surface phenotype, which appeared to be consistently confined to an order of depth of circa 1 mm. It was notable that the PLFA 16:0 was consistently associated with discrimination between phenotypes between soil surface layers. Calculation of the ratio of fungal to bacterial PLFA biomarkers showed a consistently higher ratio of fungi to bacteria present in the soil surface layer to a depth of circa 1 mm, providing evidence that fungi grow preferentially over the soil surface compared to through the soil matrix. Further investigation demonstrated that light, particularly at photosynthetically active wavelengths, was the main driving factor in the establishment of the distinct soil surface phenotypes. The inocula which drove the formation of such soil-surface community phenotypes, especially the photoautotrophic components, was demonstrated to derive predominantly from aerial sources. Functionally the nature of the soil surface community was found to affect run-off generation and shear strength at the surface. There was no significant impact of the soil surface microbiota on erodibility or water infiltration rates, although whilst distinct surface phenotypes had developed in this experimental circumstance, these were relatively deficient in photoautotrophs compared to other microcosm experiments and field circumstances, and hence extrapolation of this conclusion is not sound. This project has demonstrated that a soil surface ecological niche may exist in other unexplored soil surfaces and highlights the needs to explore this possibility and to examine any associated functional consequence should such niches be found to exist.